KUALITAS FISIK PADA POTONGAN PRIMAL KARKAS SAPI KRUI BETINA DI KABUPATEN PESISIR BARAT LAMPUNG - Pangestika, Raina; Septinova, Dian; Adhianto, Kusuma (JURUSAN PETERNAKAN, FAKULTAS PERTANIAN, UNIVERSITAS LAMPUNG, 2017)
The aims of research to determine the physical quality of primal carcass female krui cattle in KabupatenPesisir Barat Lampung. This research was conducted on April until May 2017 in Pesisir Barat District Lampung. The sample used is 4 female kruicattle. The research variables are water holding capacity, cooking loss and pH. Data were analyzed using descriptive analysis. The results of the examination of 4 female kruicattles with the primal parts of brisket, loin, and round carcasses were average pH values, that is brisket (5.77), loin (5.37), round (5.40); value of WHC (Water Holding Capacity), that is brisket (44.40%), loin (56.46%), and round (49.16%); the average value of cooking loss that is brisket (31.76%), loin (47.01%), and round (36.93%). Key words: female krui cattle, meat physical quality, Pesisir Barat District